PENGARUH CAR, NPL, NIM, BOPO, SIZE DAN LDR TERHADAP KINERJA KEUANGAN DI MASA PANDEMI - Heli Lismana; Silvi Meliani; Irwan Hermawan; Vina Herdina (AKUNTANSI DEWANTARA, 2023)
This study aims to examine the effect of the variables Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Costs and Operating Income (BOPO), Net Interest Margin (NIM), SIZE and Loan to Deposit Ratio (LDR) on Return on Assets. (ROA). The population used in this study were all conventional banks in Indonesia when the covid 19 outbreak occurred, namely in the first quarter of 2019-fourth quarter of 2021. The data used was obtained from the Financial Services Authority (OJK). The population was 152 banks. The analysis technique used is multiple linear regression, classical assumption test which includes normality test, heteroscedasticity test, multicollinearity test and autocorrelation test. and hypothesis testing using t-statistics to test the partial regression coefficients and F-statistics to test the effect together with a level of significance of 5%. The results of this study where CAR, BOPO, NIM and LDR partially affect ROA because the sig value is < 0.05, while NPL and Size have no effect on ROA because the sig value is > 0.05. even so if it simultaneously states that CAR, NPL, BOPO, NIM, SIZE and LDR affect ROA.